Effects of patients' quality of alimentation on long term clinical and anthropometric measurements after bariatric surgery - Erdem, Nihal Zekiye; Yurdakul, Cüneyt; Anuk, Turgut; Avşar, Fatih Mehmet (Springer, 2016)
[Abstract Not Available]
21st World Congress of International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO) -- SEP 28-OCT 01, 2016 -- Rio de Janeiro, BRAZIL
WOS: 000398399100357
Keywords: Gastric Banding; Food Tolerance; Quality of Alimentation